2018
DOI: 10.1186/s12885-018-5208-6
|View full text |Cite
|
Sign up to set email alerts
|

Breast diseases histologically diagnosed at a tertiary facility in Uganda (2005–2014)

Abstract: BackgroundThe prevalence and distribution of histologically diagnosed breast disease are not well documented in low income countries, Uganda inclusive. Although the greater majority of breast lesions globally are benign, breast cancer is the most frequently diagnosed cancer all over the world. We aimed at documenting the prevalence of different breast diseases histologically diagnosed at the histopathology laboratory of the Department of Pathology of the Makerere University College of Health Sciences (MakCHS L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Three studies were from Malawi, where one was a retrospective review of the registry ( 53 ) and two were retrospective cohort studies ( 66 , 68 ). There were three studies from Uganda, two were retrospective record reviews of pathology reports ( 90 , 95 ) and one was a retrospective record review of registry ( 59 ). Two studies were from South Africa, one retrospective record review ( 26 ) and a cross-sectional study of Demographic and Health Survey (DHS) data ( 125 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were from Malawi, where one was a retrospective review of the registry ( 53 ) and two were retrospective cohort studies ( 66 , 68 ). There were three studies from Uganda, two were retrospective record reviews of pathology reports ( 90 , 95 ) and one was a retrospective record review of registry ( 59 ). Two studies were from South Africa, one retrospective record review ( 26 ) and a cross-sectional study of Demographic and Health Survey (DHS) data ( 125 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gynaecomastia was the most common diagnosis, followed by fibrocystic breast disease and infiltrating ductal carcinoma. 7 By comparison, the current study identified a total of 37 males with histopathologically confirmed MBD, diagnosed with nine different pathologies, over a period of three years: invasive carcinoma was the most common histopathological diagnosis, followed by gynaecomastia. This suggests that CMJAH may diagnose more men with MBD histopathologically and see a wider variety of pathology than identified in Uganda.…”
Section: Spectrum Of Male Breast Diseasementioning
confidence: 99%
“…The most common diagnoses were proportionately different in each study. While the CMJAH Breast Imaging Department follows a strict protocol regarding which patients warrant biopsies based on their BI-RADS grading, it is not evident if the same protocol was followed in the study done by Ssemmanda et al 7 This could explain the difference between the most common diagnoses identified by each study. In the Ugandan study it is possible that a greater number of males underwent biopsies for conditions which would be diagnosed radiologically at the CMJAH Breast Imaging Unit.…”
Section: Spectrum Of Male Breast Diseasementioning
confidence: 99%
See 2 more Smart Citations